Solid Wastes Management, Biogas and Compost Generated from Organic Waste at Al-Akaider Landfill in Jordan - Fawzi al Ajlouni, Mohammad (European Journal of Applied Sciences, 2022)
Jordan has been facing a wide variety of sudden changes in humanitarian issues (population growth, industrialization rapid, urbanization process, influx of refugees to Jordan etc.). These unexpected changes forced people to make quick reactions to adapt and settle, which resulted in further generation of solid waste which normally was dumped in landfills and caused contamination of soil, water and air. Solid Waste Management (SWM) has been an integral part of every human society. Improper SWM accelerates natural resources degradation and has a great impact on climate change and the quality of life of citizens. Hence, in this paper, we highlight the environmental and health problems of the Al-Akaider landfill in Jordan. We propose a multi-pronged integrated approach to improve solid waste management at the Al Ekaider landfill. In keeping with this approach, a general action plan has been proposed that could be tailored to recycle Organic Waste (OW) to produce biogas and compost.